The Age of Capital, the Age of Utilized Capital, and Tests of the Embodiment Hypothesis - McHugh, Richard; Lane, Julia (The Review of Economics and Statistics, 1987)
Early tests of the embodiment hypothesis, which suggests that new capital is more productive than old, may have been biased due to the incorrect use of age, rather than utilized age of capital. This study, which attempts to correct for the potential mismeasurement bias by using the utilized age of capital in the analysis, finds evidence that the embodiment hypothesis is valid.